A Rare Cause of Multiple Pseudoaneurysms of Radial Artery After Coronary Angiography: Behcet's Disease - Bahar Tekin Tak; Özlem Özcan Çelebi; Orhan Küçükşahin; Sercan Tak; Ahmet Akdi; Sinan Aydoğdu (KARE Publishing, 2019)
Patients with Behçet's disease are at risk for iatrogenic aneurysms after interventions. Presently described is the case of a 55-year-old male with multiple pseudoaneurysms occurring in the late period after a coronary angiography procedure performed via the radial artery. There was no previous diagnosis of vasculitis. Behçet's disease was revealed to be the underlying pathology.